2011
DOI: 10.4238/2011.december.8.5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of sea-island cotton (Gossypium barbadense) revealed by mapped SSRs

Abstract: ABSTRACT. In order to evaluate the genetic diversity of seaisland cotton (Gossypium barbadense), 237 commonly mapped SSR markers covering the cotton genome were used to genotype 56 seaisland cotton accessions. A total of 218 polymorphic primer pairs (91.98%) amplified 361 loci, with a mean of 1.66 loci. Polymorphism information content values of the SSR primers ranged from 0.035 to 0.862, with a mean of 0.320. The highest mean polymorphism information content value for the SSR motifs was from a compound motif … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 18 publications
2
15
1
Order By: Relevance
“…Dissimilarity mean, in relation to the total accessions, was higher for Pima S7, followed by PI528329; and lower for PI528243, followed by MG04-43. This range of distance index is also close to those obtained with SSR within G. barbadense L. (WANG et al, 2011;ABDELLATIF et al, 2012).…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Dissimilarity mean, in relation to the total accessions, was higher for Pima S7, followed by PI528329; and lower for PI528243, followed by MG04-43. This range of distance index is also close to those obtained with SSR within G. barbadense L. (WANG et al, 2011;ABDELLATIF et al, 2012).…”
Section: Resultssupporting
confidence: 66%
“…Wu et al (2010) evaluated accessions from the former USSR and from Egypt, China and the USA, and observed 1.62 alleles per locus SSR, and similarity index between 0.66 to 0.94, and mean of 0.81. Wang et al (2011) also evaluated cultivars from China, and introductions from other countries, with SSR, and reported PIC between 0.03 and 0.86, and mean of 0.32. Finally, Abdellatif et al (2012) evaluate varieties and hybrids from Egypt with ISSR, EST and SSR, and reported PIC values between 0.8 and 0.91, and mean of 0.86 for SSR.…”
Section: Resultsmentioning
confidence: 99%
“…Present analysis showed significant difference among population groups, among individuals of a group and within individuals (p = 0.001). In previous similar study by Wang et al (2011), 92 % of total variation was found confined to within population variation whereas only 8 % of total variation was due to among population variation, as analyzed by AMOVA. Noormohammadi et al (2013), in diploid cotton genotypes after analysis by AMOVA, found 2 % of total variation due to population groups and 98 % due to genetic variations among accessions in each population group; such a low polymorphism among population groups could be due to inclusion of inter-specific hybrids, second backcross progenies and F 5 plants of the same cross.…”
Section: Microsatellite Diversitymentioning
confidence: 99%
“…Polymerase chain reaction (PCR), electrophoresis and silver staining were performed as previously described by Wang et al (2011).…”
Section: Ssr Marker Analysismentioning
confidence: 99%
“…DNA molecular markers were the most effective method of genetic analysis at the DNA level. In cotton, various molecular markers have been applied in genetic diversity analysis such as simple sequence repeats (SSRs), rapid amplification of polymorphic DNA (RAPD), amplified fragment length polymorphism, inter-SSR, and sequence-related amplified polymorphism; the cotton species included Gossypium hirsutum (Xu et al, 2001;Rana et al, 2005;Zhang et al, 2005;Wu et al, 2010;Kalivas et al, 2011), G. barbadense (Westengen et al, 2005;El-Zanaty et al, 2011;Wang et al, 2011), and G. arboretum (Liu et al, 2006;Kantartzi et al, 2009). …”
Section: Introductionmentioning
confidence: 99%